2014
DOI: 10.1080/10407782.2013.798550
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Heat Transfer in a Cubic Cavity Submitted to Time-Periodic Sidewall Temperature

Abstract: The laminar unsteady natural convection in a cubic cavity is comprehensively studied here using a high accuracy temporal-spatial pseudospectral method. In this study, the cavity is filled with air and one of its sidewalls is submitted to sinusoidally varying temperature, while constant lower temperature is imposed on the opposing sidewall and other sidewalls are adiabatic. Computations are performed to explore the effects of several influential factors on the fluid flow patterns and heat transfer performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 32 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Att t P = + (1) 0 , the negative temperature convects away downstream and the fluid surrounding the cylinder regains a F I G U R E 10 The variation of local Nusselt number (Nu) and isotherm contours over a period of temperature for Re = 180, α = 0.5 m , f f = 0.5 0 ∕ , a = 0.5 and (A) P = 0.01, (B) P = 0.1, (C) P = 1, (D) P = 10, (E) P = 100 F I G U R E 9 (A) Nu, ((B)-(F)) isotherm contours superimposed with streamlines during a period of temperature for Re = 180, Pr = 0.7, a = 1.5, P = 1, α = higher temperature. In this figure, Nu varies approximately in the range (−160, 170) for P = 0.01, (−100, 120) for P = 0.1, (−40, 50) for P = 1, (−14,34) for P = 10 and (−6, 30) for P = 100. The rate of heat transfer decreases as the period increases for this amplitude a = 1.5 of the pulsating temperature.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Att t P = + (1) 0 , the negative temperature convects away downstream and the fluid surrounding the cylinder regains a F I G U R E 10 The variation of local Nusselt number (Nu) and isotherm contours over a period of temperature for Re = 180, α = 0.5 m , f f = 0.5 0 ∕ , a = 0.5 and (A) P = 0.01, (B) P = 0.1, (C) P = 1, (D) P = 10, (E) P = 100 F I G U R E 9 (A) Nu, ((B)-(F)) isotherm contours superimposed with streamlines during a period of temperature for Re = 180, Pr = 0.7, a = 1.5, P = 1, α = higher temperature. In this figure, Nu varies approximately in the range (−160, 170) for P = 0.01, (−100, 120) for P = 0.1, (−40, 50) for P = 1, (−14,34) for P = 10 and (−6, 30) for P = 100. The rate of heat transfer decreases as the period increases for this amplitude a = 1.5 of the pulsating temperature.…”
mentioning
confidence: 88%
“…Their findings also suggested that increasing Rayleigh number decreased the backward heat transfer rate while the increasing temperature pulsating amplitude increased it. More detailed studies on time‐periodic pulsating temperature can be found in 29–35 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results have shown that the mean Nu and high temperature heavily depend on heating frequency and a rising of Ra reflects in energy transference enhancement. Huang et al (2014) have studied regimes of thermal convective transport in a cubic chamber having varying heated sidewall. The authors have claimed that the energy transmission augmentation is significantly dependent on Ra, sidewall pulsating period and amplitude.…”
Section: Thermal Convection and Radiationmentioning
confidence: 99%
“…In comparison to the mean heat transfer without disturbance, they found that the increase of the mean heat transfer with the disturbance is higher for shallow cavities. Finally, [30] considered a cubic cavity submitted to a sinusoidally-varying hot wall temperature. As for 2D studies, a resonance was observed for large Rayleigh numbers and was determined by the amplitude and the frequency of the disturbance.…”
mentioning
confidence: 99%